Investigasi pengaruh perawatan darurat pada sistem pelumasan engine helikopter Bell 505 Jet Ranger X di PT. Urban Air Indonesia - I Ketut Rimpung; I Nyoman Gunung (Journal of Applied Mechanical Engineering and Green Technology, 2022)
One of the important goals of tool or machine maintenance is to ensure the safety of tools and operators and users. Besides other economic goals such as extending the service life so as to increase the productivity of the tool or machine. Proper maintenance of tools or machines needs to be carried out, especially maintenance of means of transportation or transportation, both land, sea and air transportation, which can involve the safety of people and the environment at large. This research raises the problem; why and how urgent maintenance is needed on the engine lubrication system of the Bell 505 Jet Ranger X helicopter. This maintenance was carried out jointly by the technicians of the Urban Air company and students of the Department of Mechanical Engineering, Bali State Polytechnic who carried out field work practices (PKL), at PT. Urban Air Indonesia, Badung, Bali. The aims of this research are; can find the cause of a warning in the engine lubricating system known as a pope out, and can carry out appropriate maintenance according to standard procedures from the Bell 505 Jet Ranger X helicopter manufacturer. The result; maintenance was carried out according to standard procedures according to Alert Service Bulletin or ASB 506. 21 – 22 pig 1 of 5, and chips were found in the aircraft engine lubrication system oil filter. The metal flakes impede the flow of lubricating oil, so that the oil flows through the bypass pipe which causes the lubricating system pressure to rise. Then press the safety bolt which causes a pope out warning. Thus, the maintenance of the aircraft engine lubrication system can be completed within two days, and the aircraft can be operated properly and safely again.